A soft XAS transmission cell for operando studies. (17th October 2016) - Schwanke, Christoph; Xi, Lifei; Lange, Kathrin Maria
Abstract : A new design of an operando soft X‐ray transmission and fluorescence cell with capability of fast membrane replacement and easy operation compared to the previous designs is presented. The cell is suitable for studying solids, liquids and solid/liquid interfaces and manipulating the sample with electrochemical techniques and visible light. Abstract : A new cell for operando soft X‐ray absorption spectroscopy in transmission mode is presented. Developed for investigations on solar water‐splitting catalysts, the cell allows the study of solid films in direct contact with electrolyte solution while applying voltage and visible light. The design is optimized for fast sample exchange and the simultaneous measurement of fluorescence and transmission signal. The capability of the cell is presented on a manganese oxide (MnO x ) film, where electronic structure changes are monitored during forward and backward potential changes. Detailed information about the varying contributions of several Mn oxidation states during this process was revealed.